Formation Of Stress Resistance and Social Psychological Determinants of Personal Involvement in Fitness Practices - Dekhkonboeva Zulayxo Dilshod (Open Academia, 2024)
The article deals with the problems of modern High School Education related to the low level of stress tolerance among students, the general low level of physical fitness and negative coping behavior strategies. Stress is an objective and subjective component of the learning activity and is expressed in each of its components, thereby disrupting the usual rhythm and its effectiveness. Stress resistance in the article is considered from the functional point of view, as a characteristic affecting the level of productivity (or success) of the activity. Stress resistance within High School students can be formed in the process of implementing a specifically-designed technology of fitness aerobics, aimed at increasing the level of stress resistance
Keywords: stress tolerance; technology; formation